Analisa Beban Penekanan Hidrolis Terhadap Kekerasan Komposit Resin Epoksi Berpenguat Serbuk Kulit Jagung dan Fly Ash Menggunakan Metode Compression Molding - Mirza Pramudia; Teguh Prasetyo; Rifky Maulana Yusron; Mohammad Safiudin (Infotekmesin, 2024)
Using fly ash and natural fibers as environmentally friendly composite materials is expected to reduce the negative impact of fly ash as industrial waste, turning it into a material with added value. One of the methods in composite manufacturing is the compression molding method. This research aims to analyze the influence of compaction loading variations on the hardness values of epoxy composites reinforced with corn husk-fly ash powder. The research begins with producing composite specimens containing corn husk powder (20% wt) and fly ash (10% wt). The specimens are pressed with compaction loading variations of 1 ton, 2 tons, 3 tons, and 4 tons. The specimens from the compression molding are then subjected to sintering treatment at 150°C for 1 hour, followed by Shore D hardness testing. The results show that the composite material's hardness increases with the compaction loading. The highest hardness is achieved at a compaction load of 4 tons with a hardness value of 80.3 SHD. The compaction process of the composite material produces a fly ash structure that undergoes agglomeration or structural densification. This phenomenon results in an increase in the hardness of the material along with an increase in the compaction loading.